Penghindaran Pajak: Intensitas Modal dan Persediaan pada BEI Non-Cyclicals (2019-2023) - Syifa Nurul Ardiana; Intan Pramesti Dewi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study examines the effect of capital intensity and inventory intensity on tax avoidance in non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The aim is to analyze how investment in fixed assets and inventory affects tax avoidance practices. A quantitative approach is used with multiple linear regression methods and purposive sampling techniques on 73 companies. The results show that capital intensity has a negative and significant effect on tax avoidance, indicating that the greater the proportion of fixed assets, the lower the tendency to avoid taxes. Interestingly, inventory intensity also has a negative and significant effect, contrary to the initial hypothesis. Both variables simultaneously have a significant effect on tax avoidance with a determination value of 77.9% (R²=0.779). This finding suggests that companies with large investments in fixed assets and inventory tend to have higher tax compliance.